Microstrip dipole antenna analysis with different width and length at 2.4 GHz - Jamaluddin, Mohd. Haizal (2005)
This paper discusses the design and simulation of microstrip dipole antenna at 2.4 GHz. In this antenna design, Agilent's Advanced Design System (ADS) software using momentum simulation is employed to analyze the entire structure. Different width (W = 3, 5, 7, 9 mm) of the arm of dipole antenna is analyzed to study on the performance of frequency resonance. From the simulation, the wider the width will lower the resonance frequency of the antenna. Different width makes the frequency resonance of the antenna shifting lower or higher than 2.4 GHz. In this case, the length (L) of the dipole arm needs changes. Optimization value of the length is needed to make the frequency resonance at 2.4 GHz. The simulation result gives the bandwidth achieved of this microstrip dipole antenna is between 11 and 13 %. Three different width of dipole antenna have been fabricated and presented here in this paper. The properties of antenna such as input return loss and bandwidth have been investigated and compared between simulations.